115. Cathodal transcutaneous spinal direct current stimulation (tsDCS) improves motor unit recruitment in healthy subjects. Issue 4 (April 2016) - Vannini, B.; Bocci, T.; di Rollo, A.; Parenti, L.; Barloscio, D.; Vergari, M.; Priori, A.; Sartucci, F.
Abstract : Transcutaneous spinal direct current stimulation (tsDCS) is a new promising technique for modulating spinal cord function in humans. However, its effects on corticospinal pathways and lower motorneuron excitability are poorly understood. We studied the effects of tsDCS on motor unit recruitment by evaluating changes in motor unit number (MUNE) and peripheral silent period (PSP) after sham (s-tsDCS), anodal (a-tsDCS) and cathodal (c-tsDCS) tsDCS applied either over the cervical or the lower thoracic spinal cord in healthy subjects. We used the multipoint incremental technique recording from either the ulnar nerve innervated abductor digiti minimi (ADM) or the median nerve innervated abductor pollicis brevis (APB) muscle. c-tsDCS dramatically increases MUNE values, while sham and anodal polarization have no significant effects (APB: F (4, 99) = 26.4, p < 0.001; ADM: F (4, 99) = 22.1, p < 0.0001). At the same time, c-tsDCS dampened PSP respect to sham and anodal conditions ( p < 0.0001). Interestingly, also thoracic c-tsDCS significantly improved motor unit recruitment compared with both s-tsDCS and a-tsDCS (APB: F (4, 99) = 20.1, p < 0.0001; ADM: F (4, 99) = 16.6, p < 0.0001). Our data in healthy subjects suggest that tsDCS, possibly also through supraspinal effects, could provide a novel therapeutic tool in managing pathologies characterized by reduced motor unit recruitment.